Crossing in oil palm a manual - Setiawati, Umi (Techniques in plantation science series ;, 2018)
This manual discusses first the history of cultivation and breeding, as well as the pollen and embryo sac biology, fertilization, germplasm and commercial crossing, of oil palm (Elaeis guineensis). Then, guidelines in health and safety issues relating to crossing in oil palm are given, followed by protocols on pollen collection and storage; pollen viability testing; isolation of the female inflorescence; pollination; and commercial tenera production. Target audiences of this manual are students and researchers in agriculture, plant breeders, growers and end-users interested in the practicalities of oil palm crossing for breeding and commercial seed production.